The plasma chemistry of polymer surfaces : advanced techniques for surface design - Friedrich, Jorg. (Weinheim : Wiley-VCH, 2012)
'This book aims to bridge classical and plasma chemistry, particularly focusing on polymer chemistry in the bulk and on the surface under plasma exposure. The stability of surface functionalization and the qualitative and quantitative measurement of functional groups at polymer surface are featured prominently, and chemical pathways for suppressing the undesirable side effects of plasma exposure are proposed and illustrated with numerous examples. Special attention is paid to the smooth transition from inanimate polymer surfaces to modified bioactive polymer surfaces. A wide range of techniques, plasma types and applications are demonstrated'--Back cover.
Includes bibliographic references and index.
Keywords: Polymers -- Surfaces; Plasma chemistry